2017
DOI: 10.1002/syn.22016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of (‐)‐[18F]Flubatine‐specific binding: Implications for reference region approaches

Abstract: We aimed to characterize changes in binding of (-)-[ F]Flubatine to α β *-nicotinic acetylcholine receptors (α β *-nAChRs) during a tobacco cigarette smoking challenge. Displacement of (-)-[ F]Flubatine throughout the brain was quantified as change in (-)-[ F]Flubatine distribution volume (V ), with particular emphasis on regions with low V . Three tobacco smokers were imaged with positron emission tomography (PET) during a 210 min bolus-plus-constant infusion of (-)-[ F]Flubatine. A tobacco cigarette was smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The presented results should be seen in the context of previous metabolism studies on both enantiomers of flubatine and [ 18 F]flubatine [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In particular, the characterisation of phase I metabolites of (+)- 1 formed by HLM and MLM, as well as the assignment of corresponding incubated with radiometabolites in mouse, published by our group [ 4 ], are highly relevant for the discussion.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The presented results should be seen in the context of previous metabolism studies on both enantiomers of flubatine and [ 18 F]flubatine [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In particular, the characterisation of phase I metabolites of (+)- 1 formed by HLM and MLM, as well as the assignment of corresponding incubated with radiometabolites in mouse, published by our group [ 4 ], are highly relevant for the discussion.…”
Section: Discussionmentioning
confidence: 54%
“…Their development starting from the alkaloid (−)-epibatidine [ 1 ], originally isolated from the poison dart frog Epipedobates anthonyi , has been widely reported [ 2 , 3 , 4 ]. In the framework of preclinical and clinical studies, the metabolism of (−)-[ 18 F] 1 in pigs [ 5 ], rhesus monkeys [ 6 , 7 , 8 ], and in humans [ 3 , 9 , 10 , 11 ] was examined mainly with the purpose of determination of the fraction of unchanged tracer over time to enable a metabolite correction of the PET data obtained. In human, (−)-[ 18 F] 1 showed a high metabolic stability [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In former studies, we used the corpus callosum as reference region [5,9,10,13]. However, this region is difficult to delineate and in a recently published study, (−)-[ 18 F]Flubatine was displaceable by 21 ± 9% in the corpus callosum in smokers [38], indicating that at least in smokers, a relevant specific binding is available in this region which is known as the region with the lowest amount of α4β2 nAChRs in humans. Thus, the corpus callosum does not seem to be very suitable as reference region for (+)-[ 18 F]Flubatine.…”
Section: Discussionmentioning
confidence: 99%
“…A 2-18 F-FA-85380 PET study was performed on smokers. Cigarette smoking to receptor satiety revealed that nicotinic receptor displacement in the corpus callosum was relatively low, at approximately 16% (49), and in a small (2)- 18 F-flubatine PET study (n 5 3) it was approximately 21% (50). This led to the assumption that a4b2 nAChR in the corpus callosum is negligible in nonsmokers but not in smokers.…”
Section: Pet Radioligands For Imaging A4b2 Nachrsmentioning
confidence: 99%